IMPLEMENTATING THE SANGGAU REGENCY REGIONAL REGULATION POLICY NO 5 OF 2013 ON THE IMPLEMENTATION OF CHILD PROTECTION - E1011161012 Dhenie Yelsie; Zulkarnaen Zulkarnaen; Tri Hutomo (FISIP Universitas Tanjungpura, 2021)
This study aims to describe the process of implementing the Sanggau Regency Regional RegulationPolicy No. 5 of 2013 on the Implementation of Child Protection. This study used a qualitativeresearch approach. The research location was in the Department of Social Affairs, Women'sEmpowerment, Child Protection and Family Planning of Sanggau Regency. The researcher used thetheory of Jones, Charles O (Agustino, 2017:154) which explains three indicators of programimplementation or policy implementation and there are three kinds of activities that need to beconsidered carefully. The three implementation indicators consist of: 1) Organization, it can beconcluded that in order to facilitate the implementation of child protection policies and gather allOPDs in protecting and realizing children's rights and making Sanggau Regency a Child FriendlyCity; 2) Interpretation, it can be concluded that the Implementor at the Office of Social Affairs,Women's Empowerment, Child Protection and Family Planning has understood the objectives of thechild protection policy well; 3) Application,